PENERAPAN DIVERSI TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Hermanto Manurung, Boy; Noverita Simarmata, Lasmauli (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2024)
Juvenile delinquency is mostly committed by those who fail to develop their emotional souls, they cannot control themselves against new things that enter them, which gives rise to attitudes that should not be carried out. Juvenile delinquency is a manifestation of conflict that is not resolved properly during childhood or adolescence. The title of this research is the Application of Diversion to Children in Conflict with the Law Based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Problem formulation 1. How is diversion applied to children who are in conflict with the law? 2. What are the obstacles to implementing diversion for children in conflict with the law? The research method is normative juridical. The approaches used in this research are the statutory approach, conceptual approach, historical approach and case approach. The types of legal materials used are primary, secondary and tertiary legal materials. The results of this research are 1. The application of diversion to children in conflict with the law in the juvenile criminal justice system is an implementation of restorative justice to provide justice and legal protection to children in conflict with the law without neglecting criminal responsibility for the child. Deversion must be right on target and pay attention to both sides, both the victim and the perpetrator, because sometimes diversion only sees one side. If diversion is successful and the child is returned to the community, supervision by related parties such as community counselors must be carried out seriously so that the child does not re-commit criminal acts, and can follow the guidance well so that when the supervision period is over he will behave positively. 2. Obstacles to implementation Diversion towards children who are in conflict with the law, in general, is a factor of society which still wants punishment in the form of parents of children, a factor of victims who sometimes do not understand and the diversion strategy carried out by the parties involved is less than optimal.